The German-Czech Border Region after the Fall of the Iron Curtain : Effects on the Labour Market - Michael Moritz; Margit Gröger (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2006)
Using the IAB Employment Sample (IABS) covering 1980-2001 we investigate what impact the fall of the Iron Curtain has had on the skill structure of employment and wages in the western German districts neighbouring the Czech Republic. The introduction of free trade in this region, which has one of the worlds largest spatial wage differentials, can be seen as a natural experiment. We presume that changes in skill and wage structures are particularly apparent in the regions situated immediately on the open border. Distinguishing three skill categories we obtain unexpected results. Though we observe a general shift from low-skilled jobs towards skilled jobs and a convergence trend of border regions towards the national average, we do not find a special effect for the period after the opening of the border, neither concerning the skill structure nor the wage differentials. – – Unter Verwendung von Daten der IAB-Regionalstichprobe (IABS) untersuchen wir, ob nach dem Fall des Eisernen Vorhangs Qualifizierungstrends und Lohnentwicklung in den bayerischen Grenzregionen zu Tschechien signifikante Unterschiede im Vergleich mit der Entwicklung auf aggregierter staatlicher Ebene aufweisen. Der Trend zu höherer Qualifizierung sowie der Trend zu höheren relativen Löhnen für besser Qualifizierte sollten dort überdurchschnittlich messbar sein. Unsere Resultate können einen speziellen Grenzöffnungseffekt jedoch weder bei der Qualifikationsstruktur noch bei der relativen Lohnentwicklung in der Grenzregion feststellen.
Keywords: J31; R23; F16; 330; border regions; international trade; employment; wage inequality